Design of the novel bioreactors for efficient bioconversion of lignocellulose into bioethanol - Mustafa G.; Alvi A.; Batool S.T.; Ilyas H.; Zahid M.T.; Jeon B.-H.; Shafiq Z.; Abbas S.Z.; Anwar N.; Rafatullah M. (Elsevier, 2025)
The intensifying reliance on fossil fuels has spurred heightened interest in the development of sustainable alternative energy solutions, with a particular focus on bioethanol. Achieving enduring advancements in greener technologies within the biofuel manufacturing sector necessitates a harmonious integration of interdisciplinary considerations, encompassing engineering, business, sustainability, and societal aspects, to enhance the appeal of production processes for the industrial sector. Lignocellulosic ethanol, proposed as a green alternative for decades, has encountered substantial obstacles in its commercialization, including challenges in pretreatment, efficient sugar release, and fermentation. Innovative processes such as simultaneous saccharification and fermentation have been developed to surmount these hurdles. However, the engineering landscape still needs to grapple with elevated production costs hindering the establishment of lignocellulosic bioethanol plants. Bioethanol production from lignocellulosic materials involves a complex, three-stage process: pretreatment, enzymatic hydrolysis, and fermentation. Various bioreactor configurations have been explored to enhance glucose yields during enzymatic hydrolysis, with stirred tank bioreactors and membrane bioreactors being the most common. The essential criteria for bioreactor design include sufficient mass transfer, low shear stress, and adequate mixing, ensuring optimal interaction between the substrate and enzyme. This chapter delves into critical considerations for bioreactor design, addressing operational conditions, characteristics, and operating strategies of the enzymatic hydrolysis stage. This chapter offers fundamental insights, acknowledging the challenges and prospects in the field. By presenting essential information, the chapter aims to guide new researchers, equipping them with valuable insights to navigate the initial hurdles in bioethanol production research. ? 2025 Elsevier Ltd. All rights reserved.